Intermediate Algebra (6th Edition)

Published by Pearson
ISBN 10: 0321785045
ISBN 13: 978-0-32178-504-6

Chapter 7 - Review: 66



Work Step by Step

$\sqrt[3] (-32)=\sqrt[3] (-8\times4)=\sqrt[3] (-8)\times\sqrt[3] 4=-2\sqrt[3] 4$ We know that $\sqrt[3] -8=-2$, because $(-2)^{3}=-8$.
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.